Ius Constituendum Of Electronic Evidence Arrangement In Criminal Procedure Law - Lasaka, Mustalim (Universitas Negeri Gorontalo, 2023)
This research examines the legal status of electronic evidence in criminal procedures in Indonesia, highlighting the absence of its regulation within the Criminal Procedure Code (KUHAP). Electronic evidence is regulated separately from KUHAP, creating a conflict with the negative wettelijk evidentiary system, which limits evidence to the five types specified in Article 184 of the Criminal Procedure Code. The study identifies a legal gap, as some criminal laws permit electronic evidence to stand alone, while others treat it as an extension of traditional evidence. This lack of uniformity leads to legal uncertainty and overlaps in its application. The research focuses on two main issues: the legal force of electronic evidence and its potential regulation within KUHAP. Using a normative approach, including statutory, conceptual, and comparative methods, the study concludes that electronic evidence is currently categorised as